Financial Recordkeeping Training for SMEs to Enhance Business Transparency and Accountability in Central Cikarang SMEs - Fuadi, Agus; Wulandari, Tirin; Wulandari, Dian Sulistyorini; Rahman, Ibra Fatur (PT FORMOSA CENDEKIA GLOBAL, 2024)
This paper presents the implementation of a training program titled